FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA PEGAWAI DI KANTOR KESEHATAN PELABUHAN KELAS II JAYAPURA (Health Publica, 2022)
Hypertension or high blood pressure is a serious medical condition that significantly increases the risk of heart, brain, kidney, and other diseases. Hypertension is the leading cause of premature death worldwide. Based on medical check-up data from the Jayapura Class II Port Health Office, it is known that there was an increase in hypertension cases in 2020, there were 18 employees (29.03%), and in 2021 it increased to 25 employees (40.32%). This study aims to determine the factors associated with the incidence of hypertension in Jayapura Class II Port Health Office employees in 2021. This type of research is quantitative with a cross sectional study design. The sample used in this study amounted to 62 employees with a sampling technique that is total sampling. The data collection method used is in the form of primary data and secondary data, using questionnaires and medical record data for Class II Jayapura KKP employees. The data were analyzed using the chi-square test and the results showed that there was a relationship between age (p=0.014), obesity (p=0.001), exercise habits (p=0.004), workload (p=0.017), stress (p=0.001) with the incidence of hypertension in employees at the Jayapura Class II Port Health Office in 2021. Therefore, the Class II Port Health Office is expected to reduce the incidence of hypertension to carry out or hold regular blood pressure checks, morning exercise activities, lunch procurement programs every day with menus that are in accordance with balanced nutrition guidelines, making arrangements for workloads that are in accordance with the working hours that have been determined according to the law.